2007
DOI: 10.4081/ijas.2007.1s.719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of use of bread in fattening of Cinta Senese pig

Abstract: Effect of use of bakery by-products in substitution of part of a mixture of corn and seed on performance and meat traits of Cinta Senese pigs was tested. Seventeen pigs were employed: 6 pigs were fed mixture (diet M) and 11 pigs were fed mixture and bread (diet B). Each group was reared outdoors. The trial was carried out during the fattening period. Diet B showed higher average daily gain (ADG) (0.395 vs. 0.239 kg), higher backfat thickness (GM: 6.48 vs. 5.09 cm; LT: 5.67 vs. 4.28 cm) and higher inner fat dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
1
1
0
1
Order By: Relevance
“…In the present study, higher body weight gain was observed in the G2 group where 25% bread waste was added to the diet. In accordance with the present study, Sirtori et al [13] reported higher ADG in the bread waste supplemented groups. In contrast, Kwak and Kang [14] reported that neither the body weight gain nor the ADG was affected in pigs maintained on food waste mixture and that the feed efficiency decreased when larger amounts of the foodwaste mixture were incorporated into the diet.…”
Section: Resultssupporting
confidence: 81%
“…In the present study, higher body weight gain was observed in the G2 group where 25% bread waste was added to the diet. In accordance with the present study, Sirtori et al [13] reported higher ADG in the bread waste supplemented groups. In contrast, Kwak and Kang [14] reported that neither the body weight gain nor the ADG was affected in pigs maintained on food waste mixture and that the feed efficiency decreased when larger amounts of the foodwaste mixture were incorporated into the diet.…”
Section: Resultssupporting
confidence: 81%
“…Esta constatação difere do que foi observado por Sirtori et al (2007), que, ao avaliarem o consumo de resíduos de padaria, em suínos em terminação, encontraram maior ganho de peso e maior espessura de toucinho, sem prejudicar a qualidade de carne.…”
Section: Resultsunclassified
“…We identified 18 feed trials comparing the growth performance of pigs on 23 conventional and 55 food waste-based diets ( Chae et al, 2003 , Chae et al, 2000 , Cho et al, 2004 , Kjos et al, 1999 , Kumar et al, 2014 , Kwak and Kang, 2006 , Maeda et al, 2014 , Márquez and Ramos, 2007 , Mitsumoto et al, 2006 , Moon et al, 2004 , Myer et al, 1999 , Nam et al, 2000 , Ohmori et al, 2007 , Sirtori et al, 2010 , Takahashi et al, 2013a , Takahashi et al, 2013b , Takahashi et al, 2012 , Westendorf et al, 1998 ). Each feed trial evaluated how pig growth and meat quality were affected by the inclusion of food waste in pig feed; these feed trials mimicked conventional production systems where possible, using, for example, pig breeds common in modern production systems.…”
Section: Appendix D – Modelling the Effect Of Food Waste On Land Use mentioning
confidence: 99%